Numerical Simulation of Particle Erosion in Liquid-Solid Two-Phase Flow of Different T-Manifolds - JIN Long, CHEN Ji-ye, CHEN Liang (Cailiao Baohu, 2021)
At present, there are few researches on erosion caused by flow field changes at different manifolds.Based on the computational fluid dynamics(CFD)simulation technology, the erosion behavior of T-tubes with four different manifolds, i.e., common, spherical, ellipsoidal and shuttle shaped, was studied in this paper.Results showed that when the vertical pipe was the inlet pipe, and the horizontal branch pipe was the outlet pipe, it was found by intercepting the flow sections of different angles that a pair of secondary flow Dean vortices were generated in the ellipsoidal manifold only at 45° to 60° close to the pipe wall, and the other manifolds had secondary flow in the range of 30° to 90°.The erosion of common manifold mainly occurred at the connection between manifold and branch pipe, and the other manifold occurred at the reducing diameter, among which shuttle manifold was the most serious.Besides, the maximum erosion rate of different manifolds was compared and analyzed by changing the flow rate, particle mass flow rate, particle density and particle size.It was found that the maximum erosion rate of ellipsoidal manifold was the lowest and the variation range of maximum erosion rate was the smallest, which had good erosion resistance.The maximum erosion rate of shuttle manifold was the largest and fluctuated with the influence factors to the maximum.Therefore, ellipsoid manifold should be used in production, while spherical manifold and shuttle manifold should be avoided as far as possible.